Regulatory mechanism of carbohydrate metabolism pathways on oil biosynthesis of oil plant Symplocos paniculata - Wenbin Zeng; Beilei Xie; Yunzhu Chen; Jingzhen Chen; Peiwang Li; Lijuan Jiang; Changzhu Li; Qiang Liu; Yan Yang (Frontiers in Plant Science)
The mechanism underlying oil synthesis in oil plant fruits remains elusive, as sugar metabolism provides the essential carbon skeleton without a clear understanding of its intricate workings. The transcriptome and oil and sugar metabolites’ content of Symplocos paniculate, an extraordinary oil plant with immense ecological significance, were subjected to a comparative analysis throughout fruit development. The findings unveiled that the impact of sugar metabolism on oil synthesis varied throughout distinct stages of fruit development. Remarkably, during the initial phase of fruit development from 10 to 90 days after flowering (DAF), pivotal genes involved in starch biosynthesis, such as ADP-glucose pyrophosphorylase (AGP), starch synthase (SS), and starch branching enzyme (SBE), facilitated an earlier accumulation of starch within the fruit. Whereas, during the fruit maturation stage (from 90 DAF to 170 DAF), the expression of phosphofructokinase 1 (PFK-1), pyruvate kinase (PK) and pyruvate dehydrogenase (PDH) enzyme genes involved in the glycolysis pathway was significantly upregulated, thereby facilitating a rapid and substantial accumulation of oil. The sugar metabolism activity of S. paniculata fruit exerts a crucial influence on the process of oil synthesis, which is highly dependent on the specific developmental stage. These significant discoveries provide potential candidate genes for advanced genetic improvement using molecular biotechnology, thus enhancing both fruit oil production and modifying the composition of fatty acids.